Potential biological contributers to the sex difference in multiple sclerosis progression - Alvarez-Sanchez, Nuria; Dunn, Shannon E. (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is an autoimmune disease that targets the myelin sheath of central nervous system (CNS) neurons leading to axon injury, neuronal death, and neurological progression. Though women are more highly susceptible to developing MS, men that develop this disease exhibit greater cognitive impairment and accumulate disability more rapidly than women. Magnetic resonance imaging and pathology studies have revealed that the greater neurological progression seen in males correlates with chronic immune activation and increased iron accumulation at the rims of chronic white matter lesions and to more intensive whole brain and grey matter atrophy and axon loss in this sex. Studies in humans and in animal models of MS suggest that male aged microglia do not have a higher propensity for inflammation, but may become more re-active at the rim of white matter lesions as a result of either increased pro-inflammatory T cells, astrocyte activation, or iron release in the males. There is also evidence that male neurons are more susceptible to oxidative and nitrosive stress. Both sex chromosome complement and sex hormones contribute to these sex differences in biology.